2018
DOI: 10.1016/j.annepidem.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Cell phone use while driving laws and motor vehicle driver fatalities: differences in population subgroups and location

Abstract: The relationships between cell phone laws and non-alcohol-related driver fatalities are modified by driver demographics, particularly for universal hand-held bans. Universal hand-held calling bans may benefit more types of drivers compared to texting bans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Additional studies have shown differences in use rates across races and ethnic groups (2, [18][19][20][43][44][45][46]. Several of these studies found use rates to be highest among white drivers (19,20,44), while others showed that handheld talking or texting were more common among drivers identified as black or Hispanic (2, 18,43,45).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additional studies have shown differences in use rates across races and ethnic groups (2, [18][19][20][43][44][45][46]. Several of these studies found use rates to be highest among white drivers (19,20,44), while others showed that handheld talking or texting were more common among drivers identified as black or Hispanic (2, 18,43,45).…”
Section: Literature Reviewmentioning
confidence: 99%
“…To assess the effectiveness of these laws, studies have investigated the association between cellphone-related laws and driving outcomes including driver cellphone use and fatal crash rates (McCartt et al 2006 ; McCartt et al 2014 ). When specifically looking at young drivers, previous research has found that handheld calling bans were related to a 55% reduction of self-reported calling while driving (Rudisill et al 2018a ), a 58% decrease of roadside-observed phone conversations (Zhu et al 2016 ), and significant reductions in driver fatalities and the rate of involvement in fatal crashes (Lim and Chi 2013 ; Rudisill et al 2018b ). When assessing texting bans, studies have reported no significant associations between the enactment of texting bans and the reduction of self-reported engagement in texting (Rudisill et al 2018a ; Rudisill and Zhu 2015 ), and have seen inconclusive findings with reducing crash fatalities among young drivers (Rudisill et al 2018b ; Ferdinand et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…When specifically looking at young drivers, previous research has found that handheld calling bans were related to a 55% reduction of self-reported calling while driving (Rudisill et al 2018a ), a 58% decrease of roadside-observed phone conversations (Zhu et al 2016 ), and significant reductions in driver fatalities and the rate of involvement in fatal crashes (Lim and Chi 2013 ; Rudisill et al 2018b ). When assessing texting bans, studies have reported no significant associations between the enactment of texting bans and the reduction of self-reported engagement in texting (Rudisill et al 2018a ; Rudisill and Zhu 2015 ), and have seen inconclusive findings with reducing crash fatalities among young drivers (Rudisill et al 2018b ; Ferdinand et al 2014 ). Furthermore, studies have found young driver bans lack effectiveness in reducing both short-term (5 months after enactment) and long-term (2 years after enactment) observed cellphone use (Foss et al 2009 ; Goodwin et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…4,23 When speci cally looking at young drivers, previous research has found that handheld calling bans were related to a 55% reduction of self-reported calling while driving, 24 a 58% decrease of roadside-observed phone conversations, 25 and signi cant reductions in driver fatalities and the rate of involvement in fatal crashes. 26,27 When assessing texting bans, studies have reported no signi cant associations between the enactment of texting bans and the reduction of self-reported engagement in texting, 24,28 and have seen inconclusive ndings with reducing crash fatalities among young drivers. 27,29 Furthermore, studies have found young driver bans lack effectiveness in reducing both short-term ( ve months after enactment) and long-term (two years after enactment) observed cellphone use.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 When assessing texting bans, studies have reported no signi cant associations between the enactment of texting bans and the reduction of self-reported engagement in texting, 24,28 and have seen inconclusive ndings with reducing crash fatalities among young drivers. 27,29 Furthermore, studies have found young driver bans lack effectiveness in reducing both short-term ( ve months after enactment) and long-term (two years after enactment) observed cellphone use. 30,31 None of these studies assessed the combined effect of a handheld calling ban and a young driver ban in reducing self-reported talking on a phone while driving among teen drivers.…”
Section: Introductionmentioning
confidence: 99%